2023
DOI: 10.7554/elife.87253
|View full text |Cite
|
Sign up to set email alerts
|

Differential translation of mRNA isoforms underlies oncogenic activation of cell cycle kinase Aurora A

Abstract: Aurora Kinase A (AURKA) is an oncogenic kinase with major roles in mitosis, but also exerts cell cycle- and kinase-independent functions linked to cancer. Therefore control of its expression, as well as its activity, is crucial. A short and a long 3’UTR isoform exist for AURKA mRNA, resulting from alternative polyadenylation (APA). We initially observed that in Triple Negative Breast Cancer, where AURKA is typically overexpressed, the short isoform is predominant and this correlates with faster relapse times o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 81 publications
1
0
0
Order By: Relevance
“…3G ). Consistent with previous reports [ 22 , 23 ], we found that let-7a overexpression repressed KYSE-150R cell proliferation and KYSE-150R xenograft growth, while let-7a inhibition promoted KYSE-150 cell proliferation and KYSE-150 xenograft growth (Fig. 3F, G ; S4E, F ).…”
Section: Resultssupporting
confidence: 93%
“…3G ). Consistent with previous reports [ 22 , 23 ], we found that let-7a overexpression repressed KYSE-150R cell proliferation and KYSE-150R xenograft growth, while let-7a inhibition promoted KYSE-150 cell proliferation and KYSE-150 xenograft growth (Fig. 3F, G ; S4E, F ).…”
Section: Resultssupporting
confidence: 93%